2018
DOI: 10.15625/1859-3097/18/3/10642
|View full text |Cite
|
Sign up to set email alerts
|

BIODIVERSITY ASSESSMENT OF MICROORGANISMS ASSOCIATED WITH TWO MARINE SPONGES (Haliclona oculata AND Amphius huxleyi) COLLECTED AT THE LANG CO BAY OF VIETNAM

Abstract: Sponges (Phylum Porifera) are ancient sedentary and filter-feeding animals which harbour very diverse and abundant associated microbial community in their tissues with density up to 40-50% of sponge tissue volume. In this study, the diversity of associated microorganisms with two marine sponges Haliclona oculata and Amphius huxleyi collected at the Lang Co bay of Vietnam was assessed by analysis of hypervariable V3 and V4 regions of the 16S rRNA gene using Illumina MiSeq system. The taxonomic diversity of spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…To date, enzyme inhibitors have received increasing attention, not only for discovery of their structures and action mechanisms but also for potential application in different fields 1,3 . Marine sponges are known to harbor diverse microbial communities [4][5][6] and represent a prolific source of natural products from their associated microorganisms [7][8][9][10] . Recent studies have shown that many potential protease inhibitors have been isolated from sponge-associated microorganisms [11][12][13][14] ; however, the exploration and exploitation potential PIs from microorganisms are still a big challenge because almost all microorganisms are resistant to cultivation in laboratory conditions, especially symbiotic microbes.…”
Section: Introductionmentioning
confidence: 99%
“…To date, enzyme inhibitors have received increasing attention, not only for discovery of their structures and action mechanisms but also for potential application in different fields 1,3 . Marine sponges are known to harbor diverse microbial communities [4][5][6] and represent a prolific source of natural products from their associated microorganisms [7][8][9][10] . Recent studies have shown that many potential protease inhibitors have been isolated from sponge-associated microorganisms [11][12][13][14] ; however, the exploration and exploitation potential PIs from microorganisms are still a big challenge because almost all microorganisms are resistant to cultivation in laboratory conditions, especially symbiotic microbes.…”
Section: Introductionmentioning
confidence: 99%